Fungal screening and aflatoxin production by Aspergillus section Flavi isolated from pre-harvest maize ears grown in two Argentine regions - Camiletti, Boris Xavier; Torrico Ramallo, Ada Karina; Maurino, Maria Fernanda; Cristos, Diego Sebastian; Magnoli, Carina; Lucini, Enrique Iván; Gimenez Pecci, Maria De La Paz (Elsevier, 2018)
Aflatoxin contamination in maize kernels grown in central Argentina has increased since 2008. Pre-harvest maize ear samples were collected during two growing seasons to determine prevalent fungal genera as well as aflatoxin production capacity by Aspergillus sect. Flavi in two maize regions. A direct planting procedure was performed for fungal screening. Aspergillus section Flavi was identified via a morphological analysis and some colonies were isolated. Strains were subjected to molecular analysis and aflatoxin production was studied. Fusarium was the fungus genus with the highest severity, followed by Penicillium and Aspergillus in both regions. Aspergillus sect. flavi were detected in 27 (73%) samples. PCR amplifications were observed in 94% of the isolates. Aspergillus sect. flavi severity varied significantly between years. A great proportion of toxigenic strains were observed in a native Aspergillus sect. flavi population (95%) producing B- and G-type aflatoxins. Maize ears grown in regions I and IV in Argentina are prone to degradation by fungi. Toxigenic strains are predominant in native Aspergillus sect. Flavi populations. Aflatoxin contamination of maize kernels is not restricted to post-harvest; rather, it is a serious issue that begins with colonization by Aspergillus sect. Flavi in ears.